Mandibular extracellular vesicles mediate morphogenesis and mineralization of tooth germs in miniature swine through the miR-206/HDAC4 signaling axis - Cao, Xiaoyu; Ma, Duanlin; Song, Yujiao; Gao, Yiping; Liu, Wen; Du, Xiaohong; Sun, Xiaojun (Frontiers in Cell and Developmental Biology, 2026)
BackgroundReciprocal communication between odontogenic tissues underpins the complexity of tooth morphogenesis. Despite mandible serving as the developmental niche and functional platform for tooth germs, their reciprocal signaling mechanisms remain underexplored. Histone acetylation plays a pivotal role in maintaining long-term regulatory equilibrium and physiological homeostasis by establishing stable gene expression patterns. However, whether stable histone acetylation signatures exist during tooth germ morphogenesis and how they might ensure developmental fidelity remain unreported.MethodsExtracellular vesicles were isolated from E40 miniature pig mandibles, with bioinformatic analysis identifying miR-206 as a key miRNA targeting the epigenetic regulator HDAC4. Mechanistic validation utilized dual-luciferase reporter assays, qRT-PCR, and Western blotting to confirm target interactions in vitro. In vivo assessment, tooth germs were co-cultured with mandibular EVs or lentivirally transduced for miR-206/HDAC4 overexpression/knockdown, then subcutaneously transplanted into nude mice. Harvested tooth germs underwent stereomicroscopic morphological analysis, micro-CT-based 3D reconstruction with mineralization quantification, and H&E histogenesis evaluation to validate the miR-206/HDAC4 regulatory axis.ResultsIn vivo and in vitro findings collectively validated miR-206 as the critical regulator within mandibular-derived extracellular vesicles. Exosomal miR-206 suppressed HDAC4 expression in tooth germs, epigenetically mediating morphogenesis and mineralization during early stage of tooth development.ConclusionsOur identification of the exosomal miR-206/HDAC4 signal axis redefines the mandible as an active epigenetic modulator of odontogenesis. This vesicle-mediated regulation enables long-range delivery of epigenetic effectors—revealing a paradigm shift in tooth development and a druggable target for tooth regeneration.